y > 9 1/3
Step-by-step explanation:
Let the number = y
Two times a number = 2y
half the number = 1/2 (y) = y/2
half that number and 14 = y/2 + 14
Two times a number is greater than half that number and 14:
2y > y/2 + 14
we solve for y:
2y > y/2 + 14
2y - y/2 > 14
![\begin{gathered} (2(2y)-y)/(2)>\text{ 14} \\ (4y-y)/(2)>\text{ 14} \\ 4y\text{ - y > 14(2)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lbzizmgiossb0isfyvbmfuflnxwo184n0g.png)
3y > 28
y > 28/3
y > 9 1/3